Halal Awareness in Gastronomy Tourism: The Role of Fatwa in Local Dishes of Malaysia and Indonesia - Siti Syahirah Saffinee; Wan Nazri Che Mat Safiee; Mohammad Aizat Jamaludin; Setiyawan Gunardi; Luciana Anggraeni; Husna Zainal Abidin (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus